EFEKTIFITAS PENERAPAN E-TILANG TERHADAP PELAKU PELANGGARAN LALU LINTAS KENDARAAN BERMOTOR RODA DUA DI WILAYAH HUKUM RESOR KOTA PEKANBARU - ADE Inda Yani; Erdianto Effendi; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The level of public awareness is low in traffic discipline and due to the many problems in traffic, thegovernment rules are established Law No. 22 of 2009 concerning Road Traffic and Transportation. inreality the settlement of traffic cases is carried out by way of out of court or peace in a place contrary to theexisting rules of positive law. This background makes the police establish E-Tilang regulations based onarticle 272 of Law No. 22 of 2009 concerning Road Traffic and Transportation, and PERMA No. 12 of 2016concerning Procedures for Settling Traffic Violations and Law No11 of 2008 concerning Info and ElectronicTransactions. But in reality there is still illegal collection in terms of resolving traffic violation cases eventhough there are laws that regulate them. The purpose of this study is; first to find out the Factors that causethe occurrence of extortion in the settlement of traffic violation cases, both the extent of the effectiveness ofthe E-ticket in suppressing the rate of violation of two-wheeled motor vehicles in the legal area ofPekanbaru .This type of research can be classified in the type of sociological research, because in this studyimmediately conducted research on the people of Pekanbaru City and Pekanbaru Police. While thepopulation and sample are all parties related to the problem under study. In this study the data sourcesused, primary data, secondary data and tertiary data. Data collection techniques in this study were byobservation, interview, questionnaire and literature study.From the results of the research problem there are two points that can be concluded. First Thecausal factor is why there are still illegal levies in the settlement of violations of two-wheeled motor vehiclesthat Law No. 22 of 2009 concerning Road Traffic and Transportation Law No. 22 of 2009 concerning RoadTraffic and Transportation, and PERMA No. 12 of 2016 concerning Procedures for Settling TrafficViolations and Law No. 11 of 2008 concerning Information and Electronic Transactions. Not carried outproperly. Second, the effectiveness of the application of E-Tilang in reducing the level of traffic violations oftwo-wheeled motorized vehicles in the jurisdiction of the city of Pekanbaru has not been effective, it can beseen from the results of data that traffic violations are increasing. The suggestion of the author, first, is thatthe supervisor of the police is expected to pay more attention to the things that occur in the field and find outwhat are the factors that still occur in extortion. Hopes also for the community to be more disciplined intraffic and create a culture of legal order and it is expected that there are strict sanctions to the trafficpolice who still carry out illegal levies in resolving cases of traffic violations.Keywords: traffic violations – effectiveness- illegal levies